Electrochemical power sources primary & secondary batteries - Barak, M. (Institution of Engineering and Technology, 1980)
The book has 7 chapters and the first chapter deals with primary and secondary batteries which includes fuel cells and metal-air cells, the second chapter deals with definitions and basic principles, third chapter deals with primary batteries for civilian use, forth chapter deals with lead-acid storage batteries, the fifth chapter deals with alkaline storage batteries, sixth chapter deals with high temperature batteries and seventh chapter deals with room temperature cells with solid electrolytes. Appendices are given on page 483 to page 498 .